Assessment of Internship Competencies and Learning Outcomes Based on AICTE’s Examination Reforms Policy 2018 for Sustainable learning : A Case Study - Thakur, Shyamsing; Amrutsagar, Lalit Rao; Patil, Ashwini; Kulkarni, Vinay; S B, Prapulla; Malathi, P.; Nitnaware, Pravin T. (Journal of Engineering Education Transformations, 2025)
This research explores the effectiveness of assessment tools used in evaluating the competencies and learning outcomes of engineering interns, specifically within the framework of AICTE’s Examination Reforms Policy of 2018. Through the analysis of data collected from industry mentors, students, and a comparative group, the study identifies the strengths and limitations of current assessment practices. Key findings indicate that while the tools are effective in measuring core competencies and aligning with competency-based education principles, there is significant variability in ratings across different groups, suggesting a need for more tailored and context-specific assessments. The research also highlights the importance of improving mentor involvement, enhancing feedback mechanisms, and refining student self-assessments to provide a more accurate and comprehensive evaluation of intern performance. Additionally, simulations conducted to explore the robustness of these assessment tools across different scenarios confirm their general reliability but also underscore the potential for further enhancement through advanced data analytics and personalized feedback systems. Overall, this study underscores the importance of continuous improvement in assessment practices to ensure that engineering interns are well-prepared for the challenges of the modern workforce. The research concludes with recommendations for refining assessment tools, including the incorporation of soft skills evaluation, the customization of rubrics for different engineering disciplines, and the implementation of data-driven strategies to enhance educational outcomes.